Analyzing the validity and reliability of an assessment tool for senior high school students - Ikrimah; Ristati (Jurnal Pendidikan Surya Edukasi (JPSE), 2024)
This study analysed the validity and reliability of an assessment tool designed for the 1st semester of eleventh-grade students in a senior high school setting, employing a descriptive research approach. Based on the principles of validity and reliability, the analysis inspected content, face, and construct validity, along with reliability. Content validity was affirmed due to the alignment of the test items with the intended instructional objectives, face validity was ascertained through the test’s apparent measurement of its designed purpose, and construct validity was assessed by determining how effectively the tool measured the inherent characteristics it intended to measure. Using the Guttman Split-Half Coefficient, the reliability showcased a high consistency in the test scores. A detailed analysis using the Statistical Package for the Social Sciences (SPSS) confirmed the validity of the tool as all item correlation coefficients exceeded the critical value. The reliability test revealed that each instrument had scores surpassing established standards, thereby confirming the tool’s reliability. In conclusion, this study meticulously eval_uated and confirmed the content, face, construct validity, and reliability of an assessment tool aimed at senior high school students. By demonstrating alignment with the subject’s curriculum objectives and effectively measuring students’ proficiency in narrative texts, the results underscore the tool’s capability to provide educators with accurate and reliable measures of student understanding. The urgency of these findings lies in their potential to enhance assessment practices, ensuring that educational eval_uations not only reflect students’ skills and knowledge but also support their continued academic development.